Peripheral ulcerative keratitis triggered by bacterial conjunctivitis - Pokharel, A; Subedi, S; Bajracharya, M (Nepalese Journal of Ophthalmology, 2010)
Background: Peripheral ulcerative keratitis (PUK) is a disorder consisting of a crescent-shaped destructive inflammation of the perilimbal corneal stroma. Case: We present a case of PUK following acute bacterial conjunctivitis in a 60-year-old lady with a history of on-and-off joint pain for two years. After admission to the hospital, she underwent conjunctival resection and was given topical and oral steroids. She was prescribed hydroxychloroquine after confirming the diagnosis of rheumatoid arthritis with a positive RA factor. Conclusion: This report highlights the role of infection as a triggering agent in the induction of PUK in an otherwise quiescent cornea. Keywords: conjunctivitis; peripheral ulcerative keratitis; rheumatoid arthritis DOI: 10.3126/nepjoph.v2i1.3709 Nep J Oph 2010;2(1) 71-73